Associations between comorbid lumbar spinal stenosis symptoms and treatment outcomes in 6, 813 patients with knee or hip osteoarthritis following a patient education and exercise therapy program. Issue 4 (December 2022) - Young, James J.; Kongsted, Alice; Hartvigsen, Jan; Roos, Ewa M.; Ammendolia, Carlo; Skou, Søren T.; Grønne, Dorte T.; Jensen, Rikke Krüger
Abstract: Objective: People with knee or hip osteoarthritis (OA) can experience comorbid lumbar spinal stenosis (LSS), but the impact on treatment outcomes is unknown. The aim of this study was to investigate associations between comorbid LSS symptoms and changes in pain, function, and quality of life following a patient education and exercise therapy program. Design: This was a longitudinal analysis of 6813 participants in the Good Life with osteoArthritis in Denmark (GLA:D®) program; a structured patient education and exercise therapy program for knee and hip OA. Participants were classified as having comorbid LSS symptoms based on self-report symptom items. Linear mixed models were used to assess differences in change in pain, function, and quality of life outcomes (0 worst to 100 best) at 3- and 12-month follow-up. Results: 15% and 23% of knee and hip OA participants had comorbid LSS symptoms, respectively. Knee participants with comorbid LSS symptoms had smaller improvement in pain at 3-months (−1.7, 95% CI -3.3 to −0.1) and hip participants with comorbid LSS symptoms had greater improvement in function at 3- (2.5, 95% CI 0.5 to 5.0) and 12-months (3.8, 95% CI 0.9 to 6.6), when compared to those without LSS symptoms. These differences were not clinically significant and no differences in other outcomes were observed. Conclusion: Knee or hip OA patients with comorbid LSS symptoms should expect similar improvements in knee- or hip-related pain, function, and quality of life outcomes when undergoing a patient education and exercise therapy program compared to those without LSS symptoms.